The economics of orbital debris generation, accumulation, mitigation, and remediation. Issue 3 (September 2020) - Adilov, Nodir; Alexander, Peter J.; Cunningham, Brendan M.
Abstract: We explore how economic forces contribute to the generation and accumulation of orbital debris. The current structure of economic incentives for using orbital space may result in an economic Kessler Syndrome, in which orbital space becomes economically unprofitable for commercial exploration. We use simulations of an economic model to compare the effectiveness of various policy choices in slowing the accumulation rate and reducing levels of orbital debris. These findings provide useful guidance for policymakers.